2020
DOI: 10.1164/rccm.201911-2207oc
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in All-Cause Mortality with Fluticasone Furoate/Umeclidinium/Vilanterol in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Rationale: The IMPACT (Informing the Pathway of Chronic Obstructive Pulmonary Disease Treatment) trial demonstrated a significant reduction in all-cause mortality (ACM) risk with fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) versus UMEC/VI in patients with chronic obstructive pulmonary disease (COPD) at risk of future exacerbations. Five hundred seventy-four patients were censored in the original analysis owing to incomplete vital status information.Objectives: Report ACM and impact of stepping down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 183 publications
(163 citation statements)
references
References 22 publications
10
139
0
14
Order By: Relevance
“…Fluticasone/vilanterol/umeclidinium has also been shown to reduce allcause mortality with lower rates of cardiovascular and respiratory deaths. 78…”
Section: Ics-lama-labamentioning
confidence: 99%
“…Fluticasone/vilanterol/umeclidinium has also been shown to reduce allcause mortality with lower rates of cardiovascular and respiratory deaths. 78…”
Section: Ics-lama-labamentioning
confidence: 99%
“…The greater reduction in the rate and risk of exacerbations observed with FF/UMEC/VI compared with either dual therapy in the IMPACT trial [22] may therefore be expected to reduce the risk of CV mortality. The IMPACT trial demonstrated a significant 28% reduction in on−/off-treatment all-cause mortality with FF/UMEC/VI versus UMEC/VI and a non-statistically significant reduction of 11% versus FF/VI, although CV mortality has not been specifically assessed [35,36]. As the current analysis is focused on all CVAESI and only includes on-treatment events, it would be of interest to further explore the relationship between CV events, COPD exacerbations, and mortality in IMPACT in future analyses.…”
Section: Bmentioning
confidence: 99%
“…Let's Rise to the Challenge Acute exacerbations of chronic obstructive pulmonary disease (COPD) worsen the symptoms, airflow obstruction, functional disability, and quality of life, and increase mortality risk for those with the disease (1), particularly among those requiring hospitalization. Recovery from COPD exacerbations is often slow; symptoms may take months to resolve and hospital readmissions are common (1,2). Pulmonary rehabilitation (PR) is an essential component of the integrated care of individuals with COPD and other chronic respiratory diseases (3) and is effective in fostering patients' recovery after hospitalization for COPD exacerbation (4,5).…”
Section: Increasing Pulmonary Rehabilitation Uptake After Hospitalizamentioning
confidence: 99%
“…Pulmonary rehabilitation (PR) is an essential component of the integrated care of individuals with COPD and other chronic respiratory diseases (3) and is effective in fostering patients' recovery after hospitalization for COPD exacerbation (4,5). When delivered within 4 weeks of exacerbation, it improves exercise capacity, symptoms, and quality of life and reduces hospital readmission risk (4); it is recommended in disease management guidelines (1,6). Studies have also shown a survival advantage related to postexacerbation PR (4, 7).…”
Section: Increasing Pulmonary Rehabilitation Uptake After Hospitalizamentioning
confidence: 99%
See 1 more Smart Citation